Correction: Attitudes towards and experiences with economic incentives for engagement in HIV care and treatment: Qualitative insights from a randomized trial in Kenya. - Sarah Iguna; Monica Getahun; Jayne Lewis-Kulzer; Gladys Odhiambo; Fridah Adhiambo; Lina Montoya; Maya L Petersen; Elizabeth Bukusi; Thomas Odeny; Elvin Geng; Carol S Camlin (PLOS Global Public Health, 2025)
[This corrects the article DOI: 10.1371/journal.pgph.0000204.].